Preoperative radiological and electrophysiological evaluation in 100 adolescent idiopathic scoliosis patients - Hausmann, Oliver N. (Springer-Verlag, 2003)
This is a prospective study of spinal magnetic resonance imaging (MRI), electrophysiological recordings, and neurological examinations of 100 patients admitted for surgery for adolescent idiopathic scoliosis (AIS), which was conducted to assess the prevalence of structural and functional abnormalities within the spinal cord in patients with clinically normal neurologic condition. In all patients the clinical diagnosis and intact neurological condition was ascertained by a spinal orthopedic surgeon. Full-length spinal axis MRI studies (T1/T2 sequences) and somato-sensory evoked potentials of the tibial nerves (tSSEPs) were preoperatively assessed by independent evaluators blinded to the patients' medical histories. Structural spinal cord abnormalities were found in three of 100 AIS patients on MR imaging. In one patient a Chiari malformation type 1 with an accompanying syringomyelia was diagnosed, which required a suboccipital decompression. In the other two patients small thoracic syringomyelias were diagnosed. Abnormalities of spinal cord function were detected in 68% of the 100 patients: tSSEP latencies corrected for body height were increased in 56% of the patients; pathological differences between tSSEPs on the left and right sides were present in 17% (12% in combination with a prolongation of the latency). The findings of this study indicate that MRI and electrophysiological examinations are essential to assess spinal cord abnormalities that are clinically not detectable in AIS patients. Even in patients with intact neurologic condition and clinically typical right-curved thoracic scoliosis, the possibility of intraspinal pathologies should be ruled out by MRI. It is especially important to detect structural pathologies like syringomyelia and Chiari malformation before proceeding with scoliosis surgery, as these conditions are associated with a higher neurological risk during scoliosis surgery. The electrophysiological recordings made in the present study, with the high number of pathological tSSEPs, are indicative of functional abnormalities with a subclinical involvement of the recorded neuronal pathways. The relevance of the latter findings is not yet clear, but pre-operative tSSEP examinations offer the possibility of assessing alterations in spinal cord function that are undetectable by clinical examination.